JURIDICAL REVIEW OF THE MERGER OF COMPENSATION CLAIMS IN TRAFFIC ACCIDENT CASES IN KUPANG CITY AND ITS INHIBITING FACTORS BASED ON ARTICLE 98 OF THE CRIMINAL CODE IN KUPANG CLASS 1A DISTRICT COURT - Lulu, Maher Juanrez; Masu, Renny Rebeka; Resopijani, A (Law Faculty, Nusa Cendana University, 2023)
This thesis is entitled